2020
DOI: 10.30994/jceh.v3i2.59
|View full text |Cite
|
Sign up to set email alerts
|

Optimalisasi Kesehatan Penyandang Diabetes Melitus Tipe II Saat Pandemi Covid-19

Abstract: Penularan covid-19 di Indonesia menunjukkan kecenderungan terus meningkat. Covid-19 menyerang hampir seluruh kalangan usia, namun kelompok usia lanjut dan orang yang mempunyai riwayat penyakit kronis (ko-morbid) memiliki risiko lebih tinggi untuk tertular covid 19. Salah satu penyakit kronis yang dimaksud adalah diabetes. Memiliki risiko tinggi tertular covid-19, membuat penyandang DM fokus pada pencegahan covid 19 dan sering lupa untuk mengontrol kadar gula darah. Tujuan pengabdian masyarakat ini adalah untuk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 5 publications
0
5
0
6
Order By: Relevance
“…In Guan et al's study ( 2020), 7% of patient with metabolism caused by insulin action that is not adequate and well factor descendants have comorbid form of diabetes mellitus type 2. Other studies have shown patients who have factor heredity and activity low physique because follow technology work in the era of society 5.0 with diabetes mellitus have prevalence reach double compared to those who don't (Simanjuntak, Simamora, & Sinaga, 2020) .…”
Section: Studymentioning
confidence: 97%
See 2 more Smart Citations
“…In Guan et al's study ( 2020), 7% of patient with metabolism caused by insulin action that is not adequate and well factor descendants have comorbid form of diabetes mellitus type 2. Other studies have shown patients who have factor heredity and activity low physique because follow technology work in the era of society 5.0 with diabetes mellitus have prevalence reach double compared to those who don't (Simanjuntak, Simamora, & Sinaga, 2020) .…”
Section: Studymentioning
confidence: 97%
“…If sport could conducted in a manner routine so NK cells and CD8 T lymphocytes mobilization. Occur decline stress hormones so function cell cytokine proinflammatory and cells immune decrease(Blood et al., 2018) .Research bySimanjuntak et al (2020) describes society in the era of society 5.0 with factor comorbid form of diabetes mellitus feel difficulty in control diet as well To do sport. People feel lazy to exercise because dense activity room in environment profession safe for exercise in patients with diabetes mellitus(Simanjuntak et al, 2020) .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Mirawati et al, (2020) melakukan penelitian terhadap manfaat edukasi empat pilar diabetes terhadapt pengetahuan pasien akan penyakitnya, sangat membantu pasien melakukan perilaku yang positif agar mereka terhindar dari komplikasi. Edukasi lima pilar diabetes kepada penderita diabetes di era pandemi covid oleh Simanjuntak et al, (2020) membuktikan bahwa mereka terhindar dari paparan penyakit covid dan komplikasi penyakit lain.…”
Section: Pendidikan Kesehatan 5 Pilar Diabetes Ulkus Pedis Diabetik G...unclassified
“…Selain itu, mereka juga jarang minum obat, kurang melakukan aktifitas fisik dan kurang memperhatikan pola makan. Ini dapat menyebabkan kadar gula darah menjadi tidak terkontrol (Simanjuntak., Simamora., & Sinaga. 2020).…”
unclassified